Simpler semantics for computational and cognitive linguistics - Evans, Hywel (Investigationes Linguisticae, 2019)
Certain consequences are considered regarding a simpler, more cognitively plausible treatment of semantics in SignBased Construction Grammar, a cognitive, unification- based theory of language. It is proposed that a construction grammar may be able to improve its coverage of core linguistic phenomena in line with minimalist goals (Chomsky 1993). Suggestions are offered regarding relative clauses and wh-expressions to show that a more straightforward account is available, one that allows a unified treatment of scope for quantifiers and wh-expressions.